The Representations of and the Responses toward Hybridity in Indonesia: A Systematic Review - Dono Sunardi; Wawan Eko Yulianto; Lilis Lestari Wilujeng (Universitas Sanata Dharma, 2025)
This study examines the pervasive nature of hybridity in Indonesia, recognizing modern Indonesia as a nation shaped by the dynamic interaction of diverse influences. Acknowledging varying acceptance levels of this reality, the research synthesizes studies on hybridity in the country from the past fifteen years (2009-2024) to map the multifaceted landscape of hybrid identity. Through close reading and observation, the project investigates three core areas: (1) identifying primary loci where hybridity manifests; (2) exploring constituent elements contributing to hybrid identities, tracing their origins; (3) analyzing the spectrum of responses to hybridity. Analysis reveals that studies of hybrid identity in Indonesia encompass nearly all forms of cultural expression, spanning literature, culinary, architecture, music, and performance. This ubiquity highlights hybridity's deep integration into Indonesian cultural life. Contributing elements are equally diverse, drawing from Indonesia's rich tapestry of ethnic communities and global interactions shaping the archipelago over centuries. This confluence of local and global influences creates a dynamic cultural mosaic. The study finds that the dominant response to hybridity in Indonesia is one of embrace and celebration. Most research emphasizes the positive aspects of cultural fusion, highlighting the creativity and innovation born from blended traditions. However, some studies express concern about hybridity potentially threatening perceived essential values within specific cultural expressions. These contrasting perspectives underscore the ongoing dialogue surrounding hybridity in Indonesia and the need for nuanced understandings of cultural evolution. This research offers a comprehensive overview of current scholarship on hybridity in Indonesia, providing valuable insights into the dynamic interplay of cultural influences shaping Indonesia’s identity.